FACTORS INFLUENCING PROFITABILITY: A STUDY OF MINING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Muhammad Hidayat Hadi; Layyinaturrobaniyah Layyinaturrobaniyah (Jurnal Bisnis Manajemen, 2022)
The objective of this research is to empirically identify the profitability determinants of mining companies listed on the Indonesian Stock Exchange from 2015 - to 2019. Those determinants of profitability investigated in this study are Liquidity, Firm Size, Leverage, and Asset Structure with ROA as the proxy of profitability. This study employs panel data regression with Fixed Effect Model using STATA software and the result of the research found the following: (1) Liquidity has a positive impact on profitability, (2) Firm Size has a positive impact on profitability, (3) The negative impact of Leverage on profitability is not supported, (4) Asset Structure does not have a significant effect on profitability. Because the evidences suggested that liquidity is one of the drivers of profitability in mining companies in Indonesia, it is advised for these companies to reexamine their liquidity management and try to strive to achieve a balance between the benefits and risks associated with liquidity. Furthermore, leverage is also found to be, in general, positively correlated with profitability. Thus, the mining firms are suggested to fund more of their business and expansion project with debt in order to quickly raise funds and also take benefit of the debt tax shield that comes with it. However, it needs to be noted that there is a diminishing return on leverage and there is a limit where the risk of bankruptcy outweighs the benefit of the leverage, so managers should evaluate the optimal leverage for their specific companies.